2000
DOI: 10.1002/(sici)1096-8628(20000403)96:2<187::aid-ajmg13>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Association of dopamine D3-receptor gene variants with neuroleptic induced akathisia in schizophrenic patients: A generalization of Steen's study onDRD3 and tardive dyskinesia

Abstract: Neuroleptic induced akathisia is a common and distressful extrapyramidal side effect of antipsychotic treatment. A significant proportion of the variability of its development has been left unexplained and has to be attributed to individual susceptibility. Since hereditary factors have been discussed in the etiology of acute akathisia (AA), part of the individual susceptibility might be of genetic origin. Moreover, AA is regarded as a forerunner of tardive dyskinesia, a drug-induced chronic movement disorder, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
3

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(32 citation statements)
references
References 46 publications
0
29
0
3
Order By: Relevance
“…A gene 120 bp duplication and the long allele of the D4 LPR were reported to decrease the risk of TD, 204,224 increasing the evidence supporting the involvement of dopamine receptors in susceptibility to TD. The D3 Ser9Gly polymorphism was also associated with neuroleptic induced akathisia, 239 a common side effect which is thought to be triggered by alterations in nucleus accumbeus D3 activity. Other investigated dopamine receptors were not found to contribute to these adverse effects.…”
Section: Prediction Of Side Effectsmentioning
confidence: 99%
“…A gene 120 bp duplication and the long allele of the D4 LPR were reported to decrease the risk of TD, 204,224 increasing the evidence supporting the involvement of dopamine receptors in susceptibility to TD. The D3 Ser9Gly polymorphism was also associated with neuroleptic induced akathisia, 239 a common side effect which is thought to be triggered by alterations in nucleus accumbeus D3 activity. Other investigated dopamine receptors were not found to contribute to these adverse effects.…”
Section: Prediction Of Side Effectsmentioning
confidence: 99%
“…7 Also, Jö nsson et al 8 in Swedish patients with schizophrenia suggested a linkage to a DNA marker in close proximity to the DRD3 gene on chromosome 3q. Recently, a genotypic association between the DRD3 receptor polymorphism and a susceptibility to neuroleptic-induced motor disturbances such as tardive dyskinesia and akathisia in schizophrenic patients was obtained in a number of studies [9][10][11][12] except for one. 13 Furthermore, the association between the DRD3 polymorphism and a schizoaffective variant of schizophrenia was reported.…”
mentioning
confidence: 99%
“…Например, P. Eichhammer и соавт. [76] сообщили об учащении раз-вития акатизии среди носителей аллеля Gly, однако два других исследования [77,78] дали в этом отношении от-рицательные результаты.…”
Section: дофаминергическая системаunclassified